Promotion of muscle regeneration by myoblast transplantation combined with the controlled and sustained release of bFGFcpr. (1st April 2013) - Hagiwara, Koki; Chen, Guoping; Kawazoe, Naoki; Tabata, Yasuhiko; Komuro, Hiroaki
Abstract: Although myoblast transplantation is an attractive method for muscle regeneration, its efficiency remains limited. The efficacy of myoblast transplantation in combination with the controlled and sustained delivery of basic fibroblast growth factor (bFGF) was investigated. Defects of thigh muscle in Sprague–Dawley (SD) rats were created, and GFP‐positive myoblasts were subsequently transplanted. The rats were divided into three groups. In control group 1 (C1) only myoblasts were transplanted, while in control group 2 (C2) myoblasts were introduced along with empty gelatin hydrogel microspheres. In the experimental group (Ex), myoblasts were transplanted along with bFGF incorporated into gelatin hydrogel microspheres. Four weeks after transplantation, GFP‐positive myoblasts were found to be integrated into the recipient muscle and to contribute to muscle fibre regeneration in all groups. A significantly higher expression level of GFP in the Ex group demonstrated that the survival rate of transplanted myoblasts in Ex was remarkably improved compared with that in C1 and C2. Furthermore, myofibre regeneration, characterized by centralization of the nuclei, was markedly accelerated in Ex. The expression level of CD31 in Ex was higher than that in both C1 and C2, but the differences were not statistically significant. A significantly higher expression level of Myogenin and a lower expression level of MyoD1 were both observed in Ex after 4 weeks, suggesting the promotion of differentiation to myotubes. Our findings suggest that the controlled and sustained release of bFGF from gelatin hydrogel microspheres improves the survival rate of transplanted myoblasts and promotes muscle regeneration by facilitating myogenesis rather than angiogenesis. Copyright © 2013 John Wiley & Sons, Ltd.